Intermittent carbon dioxide (CO₂) injection in a sandstone reservoir in Sabah Basin - Roslan, Mohamad Hariz (2019)
The intermittent carbon dioxide (CO₂) injection is another alternative method which actually had already been used for a several cases such as heavy oil reservoir and also for the low permeability but none of this technique had been found to be used for light and intermediate oil types of reservoir. Most common problems faced for the carbon dioxide injection is the carbon dioxide breakthrough in the hydrocarbon resulting in the production of carbon dioxide higher than oil. For this simulation, the designated sandstone reservoir is located at Sabah Basin. The simulation of the intermittent of carbon dioxide injection using Petrel 2015 and Eclipse 300 has showed positive results of oil recovered and also avoiding the drawback of carbon dioxide breakthrough during injection. The results have showed that, for intermittent injection rates of 10000 MScf/day can recover for about 8.75% of oil.. Although the continuous injection have shown a higher oil recovered percentage which is 14.15% for 10000 MScf/day injection rates, however, the drawback of continuous injection is, an increase in gas injected produce back to the surface. Therefore, it can be conclude that, intermittent injection method is more efficient compare to the continuous injection, since it improve the oil recovery while avoiding the drawback of carbon dioxide breakthrough